Penerapan Metode Debat dan Model Artikulasi untuk melihat perbandingan kemampuan Berbicara Siswa kelas XI SMK Negeri Palopo - Besse Herdiana (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2019)
This research is an experimental research that aims to compare differences in students' speaking abilities using the debate method and articulation models. This study was designed with a post-test only control group desaign. This research was conducted at SMK Negeri 1 Palopo, with a population of 143 students consisting of four classes. Sampling using purposive sample technique so that the chosen ones are accounting class 1 and accounting class 2. The data obtained is data that explains the comparison of speaking skills between those who use the debate method and those who use the articulation model of students of SMK Negeri 1 Palopo, in this study, the data collected will be analyzed by using descriptive statistical techniques and parametric infrential statistics of the type of independent sample T test that is processed with a computer program Statistics Product Service Solution (SPSS). The results showed that the results of the debating method class completeness category contained 29 students who scored> 75 with a percentage of completeness (94%), and only 2 students who scored ≤ 75 with a percentage of completeness (6%). Likewise with the class using the articulation model there were 29 students who scored> 75 with a percentage of completeness (94%), and only 2 students who scored ≤ 75 with a percentage of completeness (6%). This proves that there is no significant difference between the speaking ability of class XI students of SMK Negeri 1 Palopo using the debate method and the articulation model